The Factors of Risk and Internal Control Effecting Quality of Financial Statements of the Small and Medium Enterprises in Bangkok - Mohanghva, Yupaporn; Penvutikul, Pravas (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objective of the research article were to 1) study identify risk factors 2) study effective internal controls, resulted to the quality of financial reports for Small and Medium Enterprises (SMEs) located in Bangkok for 400 Samplings. The research consisted of descriptive data analysis. These are frequency, percentage, mean, standard deviation and multilateral regression analysis was used to study procedures. The results of the research are as follows: 1. Internal risk factors in the organization in the areas of response, information and communication, and monitoring and evaluation, which is influenced on the quality of financial reports for Small and Medium Enterprises in Bangkok. Comprehension was statistically significant at level 0.01 and 0.05. 2. Risk factors in the area of events indication, control activities, information and communication, which is influenced on the quality of Financial Reports for Small and Medium Enterprises in Bangkok. Comprehensible aspect Statistically significant at levels 0.01 and 0.05. 3. Objective Identification risk factors in the organization in the areas of response, information and communication, and monitoring and evaluation, which is influenced on the quality of financial reports for Small and Medium Enterprises in Bangkok. Reliability Statistically significant at levels 0.01 and 0.05. 4. Internal Environment risk factors in the organization in the areas of objective identification, response, information and communication, and monitoring and evaluation, which is influenced on the quality of financial reports for Small and Medium Enterprises in Bangkok. Comparable aspects Statistically significant at levels 0.01 and 0.05. 5. Proper internal control in the areas of control activities, management information and communication within the organization, monitoring activities, which is influenced on the quality of financial reports for Small and Medium Enterprises in Bangkok. Understandable aspects Statistically significant at levels 0.01 and 0.05. 6. Proper internal control in the areas of control environment, management information and communication within the organization, monitoring activities, which is influenced on the quality of financial reports for Small and Medium Enterprises in Bangkok. Related to decision making Statistically significant at levels 0.01 and 0.05. 7. Proper internal control in the areas of control environment, risk assessment, management information and communication within the organization, and monitoring activities which is influenced on the quality of financial reports for Small and Medium Enterprises in Bangkok. Reliability Statistically significant at levels 0.01 and 0.05. 8. Proper internal control in the areas of control environment, and monitoring activities which is influenced on the quality of financial reports for Small and Medium Enterprises in Bangkok. Comparable aspects.